PSI-11 Evaluation of Electronically Controlled Cooling Pad Flush Rates on Heat Stressed Gilts. (7th May 2021) - Cleaver, Kristen N; Shirley, Larissa K; Field, Tyler; Hill, Brooklyn A; Kpodo, Kouassi R; Johnson, Jay S; Stwalley, Robert; Schinckel, Allan P
Abstract: This study was designed to evaluate the effects of electronically controlled cooling pads on measures of physiological responses in HS gilts. The study utilized 12 gilts randomly assigned into one of three treatment groups [Control(CN), flush 2.0 L cool water over 30 s every 4 min(F4), or flush 2.0 L over 30 s every 8 min(F8)] in a Latin Square design and replicated 12 times(2 repetitions/d over 6 d). Gilts were housed in farrowing crates and fed 1.2 kg at 0700 and 1300 h daily. On d 1 to 3(6 repetitions) the room was gradually heated from 18ºC to 32ºC, while on d 4 to 6 the room was gradually heated from 18ºC to 35ºC starting at 0730 or 1330 h. Once the temperature was achieved, cooling pads were turned on and the temperature was maintained for 2.5 h. Two baseline measurements were taken of respiration rates(RR), skin temperature through thermal imaging(IRTemp), and vaginal temperature(VTemp) before room heating began and then recorded every 20 minutes after pads were turned on. Measurements at the end of HS(PostH) and the change in values during the HS period(DIFF) were evaluated using PROC mixed of SAS. Gilts in F4 and F8 had lower RR than CN for PostH for both 32ºC and 35ºC (P< .05). DIFF in RR was less in F4 and F8 than in CN[(32ºC, P=.097) and (35ºC, P=.005)]. There was a tendency for DIFF in Vtemp at 32ºC between treatments (P=.064) but had no effect by treatment for PostH (P=.534). There was no effect in PostH and DIFF for IRTemp between treatments for 32ºC and 35ºC. PostH and DIFF for VTemp were significant at 35ºC (P=.009 and P=.001). PostH for RR was different at 35 ºC and 32 ºC (P=.0074; P=.0472) with F4 and F8 lesser and CN. In conclusion, cooling pads, regardless of flush rate, had positive impacts on physiological indicators of HS.